2021
DOI: 10.1021/acs.jpcb.1c00432
|View full text |Cite
|
Sign up to set email alerts
|

Coarse-Grained Simulations of DNA Reveal Angular Dependence of Sticky-End Binding

Abstract: Annealing between sticky ends of DNA is an intermediate step in ligation. It can also be utilized to program specific binding sites for DNA tile and origami assembly. This reaction is generally understood as a bimolecular reaction dictated by the local concentration of the sticky ends. Its dependence on the relative orientation between the sticky ends, however, is less understood. Here we report on the interactions between DNA sticky ends using the coarse-grained oxDNA model; specifically, we consider how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…oxDNA, a simulation platform to implement the coarse‐grained DNA model, has been widely used for describing a wide variety of biophysical properties of DNA, characterizing a number of DNA nanostructures. [ 31 ] First, the distance distribution of bases a and b which tend to bind was investigated through long‐term analysis of structural movements (Figure 1B). In this process, we mainly analyzed the distance variation of the two complementary bases selected on the probe from the initial relaxation conformation to the stable hybridization binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…oxDNA, a simulation platform to implement the coarse‐grained DNA model, has been widely used for describing a wide variety of biophysical properties of DNA, characterizing a number of DNA nanostructures. [ 31 ] First, the distance distribution of bases a and b which tend to bind was investigated through long‐term analysis of structural movements (Figure 1B). In this process, we mainly analyzed the distance variation of the two complementary bases selected on the probe from the initial relaxation conformation to the stable hybridization binding.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the studied biomarkers are abnormally expressed in NSCLC. [ 26–53 ] We collected 10 groups of clinical samples. Every group included tumor tissues, tumor‐adjacent tissues, and normal control tissues of NSCLC patients ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…With our bow design, x 0 also corresponds to the equilibrium extension of the ssDNA bow-string, and therefore its value will depend on both the bow size as well as whether the probe is bound to the complementary target segment. To find a realistic value of x 0 , we performed oxDNA2 simulations [53-55] for all possible combinations of bow size, target sequence, and probe state (bound or unbound). DNA bows bound to an RNA probe were not simulated; while oligomeric RNA-DNA duplexes have a slightly smaller helical rise [56], the overall effect that this difference would have on the force is negligible.…”
Section: Methodsmentioning
confidence: 99%
“…With our bow design, x 0 also corresponds to the equilibrium extension of the ssDNA bowstring, and therefore its value will depend on both the bow size as well as whether the probe is bound to the complementary target segment. To find a realistic value of x 0 , we performed oxDNA2 simulations [53][54][55] for all possible combinations of bow size, target sequence, and probe state (bound or unbound). DNA bows bound to an RNA probe were not simulated;…”
Section: B Dna Bow Assaymentioning
confidence: 99%